2001
DOI: 10.1128/jcm.39.2.651-657.2001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MB/BacT ALERT 3D System with Radiometric BACTEC System and Löwenstein-Jensen Medium for Recovery and Identification of Mycobacteria from Clinical Specimens: a Multicenter Study

Abstract: The MB/BacT ALERT 3D System (MB/BacT) (Organon Teknika, Boxtel, The Netherlands) is a fully automated, nonradiometric system with a revised antibiotic supplement kit designed for the recovery of mycobacteria from clinical specimens. In a multicenter study, the recovery rate of acid-fast bacilli (AFB) and the mean time to their detection from clinical specimens was determined by using the MB/BacT system. Data were compared to those assessed by the radiometric BACTEC 460 system (B460) and by culture on Löwenstei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 22 publications
6
40
0
4
Order By: Relevance
“…The sediment of the centrifuged CSF was added to 50 µl rates of 91% to 94% of BacT/ALERT [16][17]. The contamination rates of BacT/ALERT and the LJ culture in our study were found to be 5.8% and 7.2% respectively.…”
Section: Possible Tbm: (I) Clinical Criteria (A)mentioning
confidence: 47%
“…The sediment of the centrifuged CSF was added to 50 µl rates of 91% to 94% of BacT/ALERT [16][17]. The contamination rates of BacT/ALERT and the LJ culture in our study were found to be 5.8% and 7.2% respectively.…”
Section: Possible Tbm: (I) Clinical Criteria (A)mentioning
confidence: 47%
“…Each method has its own advantages and disadvantages, starting from the LJ medium and the Middlebrook 7H 10 medium (MB7H10) to the present trendy and speedy automated methods like the MB/BACT 3D device [8][9][10][11][12][13]. MB/BACT is a safer and a quicker method as it is an automated method which involves liquid media and as it does not involve any radioactive material.…”
Section: Resultsmentioning
confidence: 99%
“…Damle and Kaundinya found that the Nassau's swab method of decontamination was superior to Pettroff's method and the NALC method in giving positive cultures. The study of Claudio Peirsiomoni et al, has also reported a variation in the culture yield when different decontamination methods were used [25]. We included the modified Petroff's method in our study.The previous antitubercular treatment and its duration is an important determining factor for the isolation of MTB.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated higher bacterial contami- on April 7, 2019 by guest http://jcm.asm.org/ nation rates with predominantly gram-positive organisms in the MB/BacT system than with other methods, despite the addition of vancomycin to the MAS (1,2,6,8,11,12). This study evaluated the MAS concentration of vancomycin and compared the manufacturer's recommended protocol with another method in an effort to decrease bacterial contamination in the MB/BacT system.…”
mentioning
confidence: 98%